2009
DOI: 10.1016/j.jpolmod.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Does external debt lead to economic growth in Pacific island countries

Abstract: With

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 21 publications
(25 reference statements)
3
35
1
Order By: Relevance
“…Contrary to the above findings, Jayaraman and Lau (2009) found that higher debt levels can promote higher economic growth. Their study involves six Pacific island countries, covering the period 1988-2004, and is based on regressing external debt stock, exports and the budget deficit (all as a percentage of GDP) against GDP.…”
Section: The Relationship Between External Debt and Economic Growth: contrasting
confidence: 87%
“…Contrary to the above findings, Jayaraman and Lau (2009) found that higher debt levels can promote higher economic growth. Their study involves six Pacific island countries, covering the period 1988-2004, and is based on regressing external debt stock, exports and the budget deficit (all as a percentage of GDP) against GDP.…”
Section: The Relationship Between External Debt and Economic Growth: contrasting
confidence: 87%
“…The rhetoric has always been is external debt necessary for the progress of countries? Findings on external debt and economic growth has been diverse and contradictory especially on accounts of the metric used in measuring external debt (for-instance debt outstanding or debt service), the empirical approach used and also the channel used (savings and investment as a channel).Notable findings in this regard are Jayaraman and Lau (2009); Warner (1992) who found a positive impact of external debt on growth. Reinhart and Rogoff (2010); Were (2001); Iyoha (1999); Fosu (1999); Elbadawi et al (1996) found a negative relationship between external debt and growth.…”
mentioning
confidence: 99%
“…Vietnam production depends heavily on imports, especially the import of machinery and raw materials, which account for more than 90% total import revenue (GSO, 2016). Thus, using total value of exports and imports to GDP will be double counting (Nguyen, 2012); (2) This indicator was also used by Jayaraman and Lau (2009) to represent the openness of the economy when studying the effects of external debt on economic growth of Pacific countries.…”
Section: Methodsmentioning
confidence: 99%